Development of Green UV-Vis Method for Direct Determination of Total Sugars in the Aqueous Extract of Teff (Eragrostis tef (Zuccagni) Trotter) Grains and Other Cereals - Hagos Yisak; Hagos Tukue; Mesfin Redi-Abshiro; Bhagwan Singh Chandravanshi; Estifanos Ele Yaya (International Journal of Analytical Chemistry)
There is no ultraviolet visible (UV-Vis) spectrophotometric method for the direct determination of total sugars in the aqueous extract of teff grain samples. Therefore, the objective of this study was to develop a green UV-Vis spectrophotometric method to determine total sugars in the aqueous extract of white teff, brown teff, white rice, and red wheat grain samples. The calibration curve was established in the range of 20.11–7,907 mg/L using sucrose as a standard with R2 = 0.9996. The limit of detection and limit of quantification were 4.4 and 14.6 mg/L, respectively. The relative standard deviation (6.9%) of the method for the sucrose standard was within the acceptable range indicating that the method is precise. The amount of total sugars determined in the white teff (5.48–9.44% (w/w), brown teff (6.17–10.32% (w/w)), white rice (3.19% (w/w)), and red wheat (9.22% (w/w)) grain samples was comparable with other reported cereal grains. Furthermore, the accuracy of the developed analytical method was also evaluated by spiking the known amount of the sucrose standard solution to the white teff, brown teff, white rice, and red wheat sample extracts, and percentage recoveries found were in the acceptable range (85 ± 2 − 105 ± 4%) with an average recovery of 93%, confirming that the new green method is quantitatively reproducible. Hence, a fast, simple, inexpensive, widely used, selective, sensitive, precise, and accurate green UV-Vis method was developed and validated for the direct determination of total sugars in the aqueous extract of teff, white rice, and red wheat grain samples.